Genetic characterization of Ichthyoelephas longirostris La Miel and Ranchería Rivers using markers microsatellites (Orinoquia, 2014)
The Ichthyoelephas longirostris, commonly known as Pataló, is an endemic species from the Magdalena River and Rancheria River in Colombia. It is facing a b commercial and consumer fishing pressure. According to the red book of freshwater fishes of Colombia, it is identified as an endangered species due to b changes in its habitat, mainly caused by pollution and erosion. In this research, given its importance and the lack of genetic information reported, six microsatellite markers were analyzed to determine the degree of genetic variability and population structure of Pataló from La Miel and Rancheria rivers. For the two locations the expected heterozygosity ranged from 0.6182 to 0.546, the observed heterozygosity from 0.6812 to 0.454, allelic richness between 6.760 and 4.640, and the gene diversity ranged between 0.631 and 0.540, respectively. The Fis inbreeding index showed an excess of heterozygotes given its average negative value. The analysis howed two distinct populations of Pataló with moderate genetic structure, which exhibit a good genetic status. These results are of great value, given that this is the first study of genetic characterization conducted in this species. Based on these results control and management measures can be taken, relevant for repopulating actions being implemented with regard to reproduction in captivity.
Keywords: Freshwater fish; population structure; conservation; genetic variability